Kontrak Sosial menurut Immanuel Kant: Kontekstualisasinya dengan Penegakan HAM di Indonesia - Pesurnay, Althien John (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2021)
This article addresses the sensitive topic of human rights issues in Indonesia through a Kantian analysis. Cases of human rights violations are a common occurrence in Indonesia. Presently, human rights violations in the country are assessed from historical and legal perspectives. However, there is little commitment or willingness on the part of the Indonesian government to protect and defend the principles of human rights. This article is attempts to utilize arguments from political philosophy that can contextualize the protection and implementation of human rights in Indonesia, through an analysis of the concept of social contract in Immanuel Kant’s political philosophy. According to Kant, freedom and equality are natural rights. This article demonstrates that Kant's social contract theory is linear with his formal moral philosophy. In his explanation, ‘contract’ is unified will. Therefore, the Indonesian state with its power is responsible to implement the will of the public to ensure order and rule of law and to protect the rights and freedom of each individual.